A developing country perspective on vaccine-associated paralytic poliomyelitis - T. Jacob John
When the Expanded Programme on Immunization was established and oral poliovirus vaccine (OPV) was introduced for developing countries to use exclusively, national leaders of public health had no opportunity to make an informed choice between OPV and the inactivated poliovirus vaccine (IPV). Today, as progress is made towards the goal of global eradication of poliomyelitis attributable to wild polioviruses, all developing countries where OPV is used face the risk of vaccine-associated paralytic poliomyelitis (VAPP). Until recently, awareness of VAPP has been poor and quantitative risk analysis scanty but it is now well known that the continued use of OPV perpetuates the risk of VAPP. Discontinuation or declining immunization coverage of OPV will increase the risk of emergence of circulating vaccine-derived polioviruses (cVDPV) that re-acquire wild virus-like properties and may cause outbreaks of polio. To eliminate the risk of cVDPV, either very high immunization coverage must be maintained as long as OPV is in use, or IPV should replace OPV. Stopping OPV without first achieving high immunization coverage with IPV is unwise on account of the possibility of emergence of cVDPV. Increasing numbers of developed nations prefer IPV, and manufacturing capacities have not been scaled up, so its price remains prohibitively high and unaffordable by developing countries, where, in addition, large-scale field experience with IPV is lacking. Under these circumstances, a policy shift to increase the use of IPV in national immunization programmes in developing countries is a necessary first step; once IPV coverage reaches high levels (over 85%), the withdrawal of OPV may begin.